Synergy of Geological Science and Quranic Literacy in Developing a Disaster Mitigation Curriculum Based on Religious Values - Arif Muzayin Shofwan; Muhammad Yani; Endah Prapti Lestari (Institut Bahri Asyiq Galis Bangkalan, 2025)
This study was motivated by the increasing risk of geological disasters in Indonesia and the lack of systematic integration between geological science and Qur’anic literacy within value-based disaster mitigation curricula. This gap indicated the need for curriculum reconstruction that not only emphasized scientific and cognitive dimensions but also incorporated values and character formation. The study aimed to analyze the conceptual needs and to construct a disaster mitigation curriculum model based on the synergy between geological science and Qur’anic literacy. A descriptive qualitative approach with a systematic meta-analysis design was employed, examining scholarly publications from 2017 to 2025 retrieved from reputable academic databases. Data were analyzed using content analysis and thematic analysis to synthesize patterns of integration identified in the literature. The findings revealed that the integration of science and religious values in disaster mitigation education remained partial and had not yet been formulated into an operational curriculum model. This study produced an integrative conceptual model that combined epistemological foundations, curriculum structure, and character-oriented mitigation outcomes, contributing theoretically to interdisciplinary curriculum development and practically to value based disaster education.